2015
DOI: 10.1111/mec.13286
|View full text |Cite
|
Sign up to set email alerts
|

The southwestern Carpathians as an ancient centre of diversity of freshwater gammarid amphipods: insights from the Gammarus fossarum species complex

Abstract: Gammarus fossarum is a diverse species complex of epigean freshwater amphipods throughout Europe. Due to their poor dispersal capabilities and ubiquity, these crustaceans may serve as a model for investigating the influence of historical factors on the contemporary distribution and diversity patterns of freshwater macrozoobenthos. Here, we investigate the fine-scale phylogeographic structure of this complex across its range in the southwestern Carpathian Mountains, which comprises two areas that are geographic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
81
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(92 citation statements)
references
References 78 publications
11
81
0
Order By: Relevance
“…There was a substantial lag in the application of tree‐based methods. The generalized mixed Yule‐coalescent (Pons et al., ), multilocus coalescent (Rannala & Yang, ; Yang & Rannala, ) and Poisson tree process models (Zhang et al., ) were used in only seven studies (Copilaş‐Ciocianu & Petrusek, ; Esmaeili‐Rineh, Sari, Delić, Moškrič, & Fišer, ; Katouzian et al., ; King & Leys, ; Murphy, King, & Delean, ; Weiss, Niklas, Anna, & Florian, ; Yang et al., ). This lag in the use of tree‐based methods occurred despite 78% of the studies inferring molecular phylogenies (supporting information ).…”
Section: Taxonomic Practices In Delimiting Cryptic Speciesmentioning
confidence: 99%
See 1 more Smart Citation
“…There was a substantial lag in the application of tree‐based methods. The generalized mixed Yule‐coalescent (Pons et al., ), multilocus coalescent (Rannala & Yang, ; Yang & Rannala, ) and Poisson tree process models (Zhang et al., ) were used in only seven studies (Copilaş‐Ciocianu & Petrusek, ; Esmaeili‐Rineh, Sari, Delić, Moškrič, & Fišer, ; Katouzian et al., ; King & Leys, ; Murphy, King, & Delean, ; Weiss, Niklas, Anna, & Florian, ; Yang et al., ). This lag in the use of tree‐based methods occurred despite 78% of the studies inferring molecular phylogenies (supporting information ).…”
Section: Taxonomic Practices In Delimiting Cryptic Speciesmentioning
confidence: 99%
“…Alternative species delimitations suggested by different methods were not in conflict with each other, but differed in the degree of splitting; distance methods typically turned to be more conservative (Copilaş‐Ciocianu & Petrusek, ; Delić, Trontelj, Rendoš, & Fišer, ; Delić, Švara, et al., ; Eme et al., ; Katouzian et al., ; Weiss et al., ). In such cases, authors either provided a rough estimate of species number (Copilaş‐Ciocianu & Petrusek, ; Weiss et al., ), opted for a particular species hypothesis by ranking the efficiency of different methods (e.g., conservative ABGD was preferred over PTP and bGMYC; Katouzian et al., ), reconsidered the results within spatial context (presence of syntopy (Delić, Trontelj, et al., )) or drew on other studies to justify the choice of a particular threshold value. Unfortunately, cross‐referencing is not always appropriate because the value of thresholds depend on how genetic distances are calculated (e.g., uncorrected p, K2P, patristic distances) (Richards et al., ).…”
Section: Taxonomic Practices In Delimiting Cryptic Speciesmentioning
confidence: 99%
“…Furthermore, this detailed study revealed a 20% higher ostracod diversity than had been previously reported from Romania. Using molecular markers, Copilaş‐Ciocianu & Petrusek () were able to distinguish 16 new microendemic taxa in the freshwater Gammarus fossarum species complex (Crustacea: Amphipoda) sampled across a very small area of the Apuseni and Retezat Mountains. This high diversity had been unrecognized from conventional morphological approaches (Copilaș‐Ciocianu et al ., ).…”
Section: The Carpathians As a Biodiversity Hotspotmentioning
confidence: 99%
“…This high diversity had been unrecognized from conventional morphological approaches (Copilaș‐Ciocianu et al ., ). Importantly, the dated phylogeny suggests a very old, Tertiary divergence of the Carpathian lineages (Table ), probably triggered by intense geological subsidence of the former highland region (‘Tisza land’), resulting in the formation of the Pannonian basin and the Apuseni Mountains (Copilaş‐Ciocianu & Petrusek, ). A molecular study by Meleg et al .…”
Section: The Carpathians As a Biodiversity Hotspotmentioning
confidence: 99%
“…; Wysocka et al . ; Copilaş‐Ciocianu & Petrusek ) have shown that such diversification could have started even more than 15 million years ago (Ma) and suggested the ancient pre‐Pleistocene origin of the cryptic Gammarus species was followed by an unexpectedly long and dynamic evolutionary history, despite morphological stasis. Finally, studies by Hou et al .…”
Section: Introductionmentioning
confidence: 99%